2011
DOI: 10.1038/sc.2011.119
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up study of spinal cord injured patients after discharge from inpatient rehabilitation in Nepal in 2007

Abstract: Study design: Observational cohort study. Objectives: To evaluate ongoing health and community reintegration of patients with spinal cord injury (SCI) after discharge from inpatient rehabilitation in Nepal. Setting: Nepal. Methods: This study follows a cohort of 37 patients with SCI in Nepal, 1-2 years after discharge from inpatient rehabilitation in 2007. Participants were visited at home and data were obtained through semi-structured interviews that evaluated health, independence in daily living (Modified Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 18 publications
3
77
0
Order By: Relevance
“…34 In addition, the hospitals and clinics that performed the cited studies may not have the financial resources or infrastructure to document and report all PUs reliably. 28 Furthermore, individuals with more severe mobility impairments and those who live remotely are unlikely to be captured by such studies because of limited transportation options in many low resource communities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…34 In addition, the hospitals and clinics that performed the cited studies may not have the financial resources or infrastructure to document and report all PUs reliably. 28 Furthermore, individuals with more severe mobility impairments and those who live remotely are unlikely to be captured by such studies because of limited transportation options in many low resource communities.…”
Section: Resultsmentioning
confidence: 99%
“…Ten articles were identified that reported the prevalence or incidence of PUs in community dwellers from 6 months to 20 years after injury. [24][25][26][27][28][29][30][31][32][33] Of note, very few of these study subjects were reported to have undergone SCI rehabilitation. These 10 papers reported a PU prevalence of 26.7-46.2%, mean of 35.2%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] Some studies have also examined these issues in LMICs. [4][5][6][7] However, few studies sample in a representative way-most, instead, rely on samples of convenience. Therefore, we sought to determine the psychological and socioeconomic status, complications, and QOL in people living with SCI in Bangladesh after discharge from hospital.…”
Section: Introductionmentioning
confidence: 99%